Assessing the acceptability of individual studies that use deception: A systematic review of normative guidance documents - Verbeke, Kamiel; Krawczyk, Tomasz; Baeyens, Dieter; Piasecki, Jan; Borry, Pascal (Accountability in research, 2024)
Research participants are often deceived for methodological reasons. However, assessing the ethical acceptability of an individual study that uses deception is not straightforward. The academic literature is scattered on the subject and several aspects of the acceptability assessment are only scarcely addressed, which parallels reports of inconsistent ethics review. Therefore, we aimed to investigate where normative guidance documents agree and disagree about this assessment. A PRISMA-Ethics-guided systematic review of normative guidance documents that discuss deception of research participants was conducted. Our search strategy resulted in 55 documents that were subsequently analyzed through abductive thematic analysis. While guidance documents mention little about specific risks and opportunities of deception, our analysis describes a rich picture of the thresholds for acceptability of the risks and benefits of deception and their integration, the comparison with the risk-benefit analysis of alternative non-deceptive methods, and the bodies of people who are positioned to do the review. Our review reveals an agreement on the general process of assessing the acceptability of studies that use deception, although significant variability remains in the details and several topics are largely or completely unaddressed in guidance documents.